Asymptotical estimation of oscillatory integral - Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2009)
The oscillatory integral is important for averaging of weakly nonlinear differential systems. Uniformly valid for parameters estimation of the integral can be use for substantiation of averaging method for wave interaction modelling.
Keywords: asymptotic methods; averaging; nonlinear waves